PECULIARITIES OF THE IRRIGATION WATER DELIVERY PAYMENT IN THE REPUBLIC OF UZBEKISTAN - Muminov , Sherzod (GREEN ECONOMY AND DEVELOPMENT, 2025)
The article examines the specific features of irrigation water delivery payment in the Republic of Uzbekistan. Particular attention is given to the legal framework and methods of irrigation water delivery payment, as well as to the challenges of efficient water use under conditions of scarcity. The article emphasizes the necessity of reforming the irrigation water delivery payment system, introducing incentive mechanisms to promote the rational use of irrigation water, and improving the financial sustainability of water management organizations. Recommendations are provided for optimizing irrigation water delivery payment, enhancing transparency, and increasing private sector involvement in water resource management and efficient water use